The future of nuclear security: Commitments and actions – Power generation and stewardship in the 21st century. (November 2017) - Martin, P.G.; Tomkinson, N.G.; Scott, T.B.
Abstract: Since the terrorist events of the 11th September 2001, the world as it was once known was changed forever. It was these catastrophic terrorist actions over fifteen years ago that saw the dawn of a new era with heightened security across many everyday areas of society that had not previously witnessed such scrutiny or control. Coupling this elevated risk of physical and technical aggression with the ever-increasing global per capita energy demand – there has been witnessed a continually growing reliance on nuclear energy for baseline power generation, a form of electricity production that requires both the necessary international safeguards and controls for its safe use. As more and more of the global energy budget is provided by low-carbon sources (over highly-polluting fossil fuels), the volume of nuclear material in existence will grow substantially – requiring considerable attention and policy to ensure its long-term safety and security. This commentary describes the vast range of policy challenges faced by the nuclear industry resulting from the rapid technological advancements being made across society, and how these directly (and indirectly) affect global nuclear security, as well as providing a thorough discussion on how best these challenges may be overcome. Highlights: Commentary on the challenges in current nuclear energy generation. Policy issues faced by continued advancements in nuclear power. Risks and advantages associated with technological advancements. Review of implications of terrorist actions on nuclear safety and security.